Janus kinase inhibitors modify the fatty acid profile of extracellular vesicles and modulate the immune response (2024)
ABSTRACT: Methods: EVs were isolated from monocytes (M) and lymphocytes (L) of healthy individuals, as well as from U937 (U) and Jurkat (J) cells exposed to non-cytotoxic concentrations of BARI, ITA, and dimethyl sulfoxide (DMSO; vehicle control). The binding to and engulfment of EVs by peripheral blood leukocytes of healthy individuals were analyzed by flow cytometry using CFSE-stained EVs and anti-CD45-PeCy7 mAb-labeled whole blood. The effect of EVs on respiratory burst, T-cell activation and proliferation, cytokine synthesis, and platelet aggregation was evaluated. Respiratory burst was assessed in PMA-stimulated neutrophils by the dihydrorhodamine (DHR) test and flow cytometry. T-cell activation and proliferation and cytokine production were assessed in CFSE-stained PBMC cultures stimulated with PHA; expression of the T-cell activation markers CD25 and CD69 and T-cell proliferation were analyzed by flow cytometry, and the cytokine levels were quantified in culture supernatants by Luminex assays. Platelet aggregation was analyzed in platelet-rich plasma (PRP) samples by light transmission aggregometry. The EVs' fatty acid (FA) profile was analyzed using methyl ester derivatization followed by gas chromatography. Results: ITA exposure during the generation of EVs modified the size of the EVs released; however, treatment with DMSO and BARI did not alter the size of EVs generated from U937 and Jurkat cells. Circulating neutrophils, lymphocytes, and monocytes showed a 2-fold greater tendency to internalize ITA-U-EVs than their respective DMSO control. The neutrophil respiratory burst was attenuated in greater extent by M-EVs than by L-EVs. Autologous ITA-M-EVs reduced T-cell proliferation by decreasing IL-2 levels and CD25 expression independently of CD69. A higher accumulation of pro-inflammatory cytokines was observed in PHA-stimulated PBMC cultures exposed to M-EVs than to L-EVs; this difference may be related to the higher myristate content of M-EVs. Platelet aggregation increased in the presence of ITA-L/M-EVs by a mechanism presumably dependent on the high arachidonic acid content of the vesicles. Conclusions: Cellular origin and jakinib exposure modify the FA profile of EVs, enabling them, in turn, to modulate neutrophil respiratory burst, T-cell proliferation, and platelet aggregation. The increased T-cell proliferation induced by BARI-L/M-EVs could explain the lymphocytosis observed in patients treated with BARI. The higher proportion of arachidonic acid in the FA content of ITA-L/M-EVs could be related to the thrombosis described in patients treated with ITA. EVs also induced a decrease in the respiratory burst of neutrophils.